2016
DOI: 10.1596/1813-9450-7628
|View full text |Cite
|
Sign up to set email alerts
|

Global Migration Revisited: Short-Term Pains, Long-Term Gains, and the Potential of South-South Migration

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Although migration opponents in high-income countries have often argued that low-skilled migrants "crowd out" jobs of native workers, many studies have found that this is not the case. Ahmed, Go, and Willenbockel (2016) show that while migration can push down the wages of native workers in the short run, the long-run impacts on incomes of native-born workers is positive. These short run effects depend on the degree of substitutability of migrants' skills with those of natives.…”
Section: Figure 11: Migration Flows From South Asia Are Large and Hamentioning
confidence: 95%
See 1 more Smart Citation
“…Although migration opponents in high-income countries have often argued that low-skilled migrants "crowd out" jobs of native workers, many studies have found that this is not the case. Ahmed, Go, and Willenbockel (2016) show that while migration can push down the wages of native workers in the short run, the long-run impacts on incomes of native-born workers is positive. These short run effects depend on the degree of substitutability of migrants' skills with those of natives.…”
Section: Figure 11: Migration Flows From South Asia Are Large and Hamentioning
confidence: 95%
“…In the longer run, the wages of workers who were negatively impacted do not only recover but even exceed pre-migration wages. Overall, natives of high-income receiving countries gain the most due to larger increases in capital return and quicker capital formation (Ahmed, Go, and Willenbockel 2016). While the wages of natives with similar skills of immigrants can decline in the short run, natives with complementary skills typically benefit from an inflow of migrants (World Bank 2018).…”
Section: Figure 11: Migration Flows From South Asia Are Large and Hamentioning
confidence: 99%
“…As migrant-sending countries develop and inequality within recipient countries declines, the economic incentives for migration could become less pronounced. High-income countries tend to be the most popular destinations for migrants, and most migrants come from developing countries (Ahmed, Go, and Willenbockel 2016). 6 The broader impact of development on migration, however, depends on the patterns of growth.…”
Section: The Main Drivers Of Demographic Changementioning
confidence: 99%
“…• Are host communities expected to shoulder added burdens placed upon their resources (OECD 2012), or are the refugees portrayed as labour and cultural dividends (Ahmed et al 2016)?…”
Section: Key Themes In Conflict-induced Migrationmentioning
confidence: 99%